Levels and effectiveness of oral retinol supplementation in VLBW preterm infants. (December 2018) - Garofoli, Francesca; Mazzucchelli, Iolanda; Decembrino, Lidia; Bartoli, Antonella; Angelini, Micol; Broglia, Monica; Tinelli, Carmine; Banderali, Giuseppe; Stronati, Mauro
Retinol palmitate oral administration is convenient, but it is difficult to assess/monitor its nutritional status in preterm infants and literature is controversial about the administration route and the effectiveness of vitamin A supplementation. We primarily evaluated retinol plasma levels to assess the vitamin A nutritional status in preterm infants (<1500 g; 32 weeks) after 28 days of oral supplementation (3000 IU/kg/day, retinol palmitate drops), in addition to vitamin A standard amount as suggested by European Society of Paediatric Gastroenterology, Hepatology and Nutrition (ESPGHAN) guidelines. We then observed the rate of typical preterm pathologies in the supplemented group (31 newborns) and in 10 matching preterm infants, hospitalized in neonatal intensive care unit (NICU) in the same period, who received neither vitamin A supplementation nor parents allowed plasma sampling. Oral integration resulted in constant retinol plasma concentration around the desired level of 200 ng/mL, but without statistical increase during the study period. Due to the complexity of vitamin A metabolism and the immaturity of preterm infant's organs, retinol supplementation may had first saturated other needy tissues; therefore, plasmatic measures may not be consistent with improved global vitamin A body distribution. Therefore, achieving a constant retinol concentration is a valuable result and supportive for oral administration: decreasing levels, even after parenteral/enteral supplementation, were reported in the literature. In spite of favourable trend and no adverse events, we did not report statistical difference in co-morbidities. This investigation confirms the necessity to perform further trials in preterm newborns, to find an index reflecting the complex nutritional retinol status after oral administration of vitamin A, highlighting its effectiveness/tolerability in correlated preterm infant's pathologies.